2010
DOI: 10.1007/s10641-010-9709-7
|View full text |Cite
|
Sign up to set email alerts
|

Sound production in the whitemouth croaker and relationship between fish size and disturbance call characteristics

Abstract: The whitemouth croaker produces two different sounds using extrinsic sonic muscles: (1) male advertisement calls during the spawning season and (2) disturbance calls, produced by both sexes. The advertisement call, related to courtship, was recorded in the field and from two marked spawning males of 28 and 30.5 cm L T in the laboratory. It consists of individual pulses with average durations of 19.7 ms and 17.8 ms for the two males respectively, interpulse intervals of 496 ms and 718 ms, and dominant frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 35 publications
2
55
0
Order By: Relevance
“…Larger fish emitted deep and strong grunts whereas smaller fish emitted sounds with a higher frequency. The fundamental frequency also decreases with fish size in the weakfish (Connaughton et al, 2000;Connaughton et al, 2002) and the whitemouth croaker (Micropogonias furnieri) (Tellechea et al, 2010). Fine et al (Fine et al, 2004) suggested therefore that croakers could estimate relative size of the caller equally in aerial and underwater recordings.…”
Section: Research Articlementioning
confidence: 99%
“…Larger fish emitted deep and strong grunts whereas smaller fish emitted sounds with a higher frequency. The fundamental frequency also decreases with fish size in the weakfish (Connaughton et al, 2000;Connaughton et al, 2002) and the whitemouth croaker (Micropogonias furnieri) (Tellechea et al, 2010). Fine et al (Fine et al, 2004) suggested therefore that croakers could estimate relative size of the caller equally in aerial and underwater recordings.…”
Section: Research Articlementioning
confidence: 99%
“…More-detailed comparative studies on at least the swimbladder, scutes and pectoral girdles are required to understand these data. In the whitemouth croaker, Micropogonias furnieri, sound characteristics correlated with size in smaller fish, but were independent among larger size classes (Tellechea et al, 2010). The sound production mechanism in whitemouth croaker involves sonic muscles acting directly on the swimbladder and thus the reason for the similar size-ontogeny relationship with sound may be different from that of R. rectangulus.…”
Section: Discussionmentioning
confidence: 87%
“…Extrinsic sonic muscles of M. furnieri generate disturbance calls produced by both sexes and advertisement or courtship calls produced exclusively by males (Tellechea et al, 2010). These two types of sounds were also reported in intrinsic sonic muscles of the black drum P. cromis (Locascio et al;Tellechea et al, 2011).…”
Section: Discussionmentioning
confidence: 60%
“…In M. furnieri as well as in other sciaenids, the sonic muscle associated to the bladder is found in both sexes (Ueng et al, 2007;Tellechea et al, 2010;2011), but males and females sounds have different frequencies. Extrinsic sonic muscles of M. furnieri generate disturbance calls produced by both sexes and advertisement or courtship calls produced exclusively by males (Tellechea et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation